2005
DOI: 10.1002/jrs.1371
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopic study of pottery fragments from the Lapatsa tomb, Cyprus, ca 2500 BC

Abstract: Micro-Raman spectroscopy was applied to the mineralogical characterization of Bronze Age Cypriot ceramic fragments from the Lapatsa Tomb collection of the Ringling Museum of Art. Micro-probing was carried out on the surface and the results were compared with those of micro-probing from the crosssection of the two samples studied. Significant statistics were collected from 500 locations on each sample. Various phases were identified: quartz, albite, calcite, ilmenite, anatase, rutile, hematite and maghemite. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…The presence of the mineral albite, (belonging to the plagioclass group: NaAlSi 3 O 8 -CaAl 2 Si 2 O 8 ) characterized by the lowest concentration of calcium (0-10%), [37] is found in most of the pottery samples. Identification of low-temperature albite confirms that the firing temperature was below 950 • C. [36] The presence of CaCO 3 bands detected in the Raman as well as in the IR spectra of the examined pottery shards is additional evidence that the pottery finds were fired at moderate firing temperature.…”
Section: Mineralogical Composition Of the Ceramic Bodymentioning
confidence: 71%
See 1 more Smart Citation
“…The presence of the mineral albite, (belonging to the plagioclass group: NaAlSi 3 O 8 -CaAl 2 Si 2 O 8 ) characterized by the lowest concentration of calcium (0-10%), [37] is found in most of the pottery samples. Identification of low-temperature albite confirms that the firing temperature was below 950 • C. [36] The presence of CaCO 3 bands detected in the Raman as well as in the IR spectra of the examined pottery shards is additional evidence that the pottery finds were fired at moderate firing temperature.…”
Section: Mineralogical Composition Of the Ceramic Bodymentioning
confidence: 71%
“…Significantly smaller amount of rutile detected in those samples most probably originated from the clay ore and not as a result of high-temperature firing transformation. [36] Plagioclases. The presence of the mineral albite, (belonging to the plagioclass group: NaAlSi 3 O 8 -CaAl 2 Si 2 O 8 ) characterized by the lowest concentration of calcium (0-10%), [37] is found in most of the pottery samples.…”
Section: Mineralogical Composition Of the Ceramic Bodymentioning
confidence: 99%
“…Chinese celadon sherds of the Longquan type, excavated in 1934 from Mapungubwe Hill, Zimbabwe, and dating from the Yuan (1279e1368) or early Ming (1368e1644) periods, were also shown by XRF and RM to contain both anatase and rutile, despite the fact that the weight percentages of TiO 2 present are very low (0.13e0.20 wt%) (Prinsloo et al, 2005). Both anatase and rutile have also been identified by RM in Bronze Age ceramic fragments from the Lapatska Tomb collection in Cyprus (Sendova et al, 2005). In yet further studies, both anatase and rutile have been identified by RM as componentsdalbeit also at minor levels (c. 1.5 wt% total TiO 2 by SEM/EDX)dof a white paint from a Roman ceramic pot (Middleton et al, 2005) and broken pots (Edwards et al, 2006) in the English Midlands (Castor and Eastern Maudit, respectively), the fine matrices having a composition which is consistent with their being predominantly a poorly crystalline mixture of aluminosilicates.…”
Section: Anatase In Ceramicsmentioning
confidence: 88%
“…Sherd 10(3) also contained a small amount of anatase and ilmenite, FeTiO 3 (Fig. 4e,f) (Sendova et al, 2005). The finding of rutile in the body of both sherds could suggest that the firing of each may have been carried out at a higher temperature than was that of the white slip, i.e.…”
Section: Black Decoration and Red-brown Bodymentioning
confidence: 95%
“…Different components are identified by the Raman measurements on the teal tesserae as shown in Fig. 3b [33]. In a red/brown spot in the translucent blue sample, typical bands of an iron oxide structure (haematite, aFe 2 O 3 ) appear at 220, 289, 398 and 1317 cm -1 [34,35] as shown in Fig.…”
Section: Blue Tesseraementioning
confidence: 95%